2021
DOI: 10.1177/14713012211042466
|View full text |Cite
|
Sign up to set email alerts
|

Co-designing complex interventions with people living with dementia and their supporters

Abstract: Background and objectives We engaged people living with dementia, family carers and health and social care professionals in co-designing two dementia care interventions: for family carers and people living with dementia (New Interventions for Independence in Dementia Study (NIDUS)-family and home-care workers (NIDUS-professional training programme). Research design and methods Over October 2019–March 2020, we invited public and patient (PPI) and professional members of our NIDUS co-design groups to complete th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The intervention co‐design process (Lord et al., 2021 ) and its theoretical basis, and how this drew on concepts of person‐centred care are described elsewhere (Lord et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention co‐design process (Lord et al., 2021 ) and its theoretical basis, and how this drew on concepts of person‐centred care are described elsewhere (Lord et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The NIDUS‐professional (New Interventions for Independence in Dementia Study) training intervention is, to our knowledge the first training and support intervention for homecare workers to be co‐designed by this staff group, their managers, health professionals, people living with dementia and their family carers (Lord et al., 2021 ) in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Full details of NIDUS-Professional content, the process of co-design and results from an initial pilot study are reported elsewhere. 11 12 The intervention is delivered online by two facilitators to groups of six to eight homecare workers. Sessions are held every two weeks for 12 weeks; each last around 1–1.5 hours and cover specific topics ( table 1 ).…”
Section: Methods and Analysismentioning
confidence: 99%
“… 9 10 Given the importance of joined-up care, we co-designed NIDUS-Professional as an evidence-based support and training programme for homecare agency staff, to be delivered alongside the NIDUS-Family intervention. 11 Our aspiration is that our interventions with homecare staff and with their clients and family carers would be synergistic, through training and supporting staff to work with their clients to reach personalised goals. After a successful pilot of the intervention, 12 we describe here the protocol for our randomised feasibility study to test the feasibility and acceptability of this training and support programme among homecare staff, people living with dementia and their family carers.…”
Section: Introductionmentioning
confidence: 99%
“…19,29,30,33,[37][38][39] In this context, review papers of studies implementing PPIE highlight the manifold opportunities for PPIE, 15 training for all stakeholders. 29,30,37,[41][42][43][44][45] While the effectiveness of and methods for successful PPIE have accordingly become an increasingly popular research topic, the developed methods are predominantly directed toward adult patients, whereas methods for integrating children into the research process are still lacking. 46 Furthermore, the awareness for and attitude toward PPIE among the various stakeholders in health care has only been investigated by few authors 12 and an even lower number of studies has focused on the complex interdisciplinary field on pediatric oncology.…”
Section: Introductionmentioning
confidence: 99%